2018
DOI: 10.1111/ppl.12770
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins modulate auxin responses during tomato (Solanum lycopersicum L.) fruit development

Abstract: In tomato, auxin and gibberellins (GAs) interact with each other to drive fruit growth and development. While the role of auxin in directing GA biosynthesis and signal is already known, very little information has been obtained about GA-mediated control of auxin signalling and response. Interestingly, we show that gibberellic acid (GA ) is able to modify the expression of several auxin signalling genes in the partial auxin-insensitive diageotropica (dgt) mutant, suggesting that GAs may override the control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…We found significantly increased expression levels of genes encoding GA and CK biosynthetic key enzymes, such as GA 20-oxidase 1 (GA20ox1) and cytokinin phosphoribohydrolase 'Lonely guy' (LOG3) ( Table 1). These results were similar to previous reports that upregulation of GA20oxs contributed to active GAs accumulation, which is required for fruit development in tomato [47,48]. The expression of SlLOG2, a CK biosynthetic gene, significantly increased after anthesis [49].…”
Section: Plos Onesupporting
confidence: 91%
“…We found significantly increased expression levels of genes encoding GA and CK biosynthetic key enzymes, such as GA 20-oxidase 1 (GA20ox1) and cytokinin phosphoribohydrolase 'Lonely guy' (LOG3) ( Table 1). These results were similar to previous reports that upregulation of GA20oxs contributed to active GAs accumulation, which is required for fruit development in tomato [47,48]. The expression of SlLOG2, a CK biosynthetic gene, significantly increased after anthesis [49].…”
Section: Plos Onesupporting
confidence: 91%
“…In tomato, gibberellins interact with auxins to drive fruit growth and development 57 . Several members of the auxin signalling pathways (ARFs and Aux/IAA) are involved in the control of cell division and expansion during early fruit development 16,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Parthenocarpy, another physiological event occurring in the absence of pollination, is characterized by intensive alterations of phytohormones such as auxin, gibberellin (GA), cytokinin or combinations thereof during fruit set ( McAtee et al, 2013 ). In fact, exogenous application of these phytohormones alone can trigger fruit development including fruit set and fruit growth, to a certain extent, and their combinations would induce a normal fruit growth in the absence of fertilization ( Srivastava and Handa, 2005 ; Mignolli et al, 2018 ). Accordingly, increased GA content or perception are associated with parthenocarpic fruits in tomato ( Solanum lycopersicum L.) mutants such as pat ( Mazzucato et al, 1998 ), pat-2 ( Fos et al, 2003 ), pat-3/4 ( Fos et al, 2001 ), whereas facultative parthenocarpic fruits are observed in the procera mutant ( Carrera et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%